Captain Seat: Smart Solution for Physical Distancing on Buses During the Covid-19 Pandemic - Muji Setiyo; Budi Waluyo (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2021)
It has been a year after the announcement of Covid-19 outbreak in Wuhan. Activity restriction, implementation of health protocol, and lock-down are enforced to cut-off the spread of this virus. However, in the uncertainty towards a new normal, the mobility of people continues for various purposes. A rapid medical check-up at the airport or at railway stations is possible by the local authorities but it is impossible for public bus passengers due to the limitations of medical staff and a large number of bus stations. Most passengers also failed to comply with the government's recommendation to conduct a rapid test before using public buses. As anticipation, the Transportation Agency issued a regulation that all buses can only be filled with 50% (max) of their normal capacity by emptying 2 of the 4 seats in a row. As a consequence, a 32-seat bus can only be filled with 16 passengers (max) and the ticket price has doubled to cover operational costs. However, passenger interest in bus services has decreased due to high ticket prices. Therefore, this short article reports the smart actions of several bus companies in Indonesia to create a